2018
DOI: 10.1038/s41598-018-26347-y
|View full text |Cite|
|
Sign up to set email alerts
|

Neuronal activity regulates DROSHA via autophagy in spinal muscular atrophy

Abstract: Dysregulated miRNA expression and mutation of genes involved in miRNA biogenesis have been reported in motor neuron diseases including spinal muscular atrophy (SMA) and amyotrophic lateral sclerosis (ALS). Therefore, identifying molecular mechanisms governing miRNA expression is important to understand these diseases. Here, we report that expression of DROSHA, which is a critical enzyme in the microprocessor complex and essential for miRNA biogenesis, is reduced in motor neurons from an SMA mouse model. We sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 75 publications
(87 reference statements)
0
21
0
Order By: Relevance
“…In regard to the contribution of CBs to miRNA biogenesis, recent work has implicated miRNA dysregulation as a contributor to spinal muscular atrophy (SMA), the leading genetic cause of infant mortality ( Goncalves et al , 2018 ). Most cases of SMA are caused by insufficient levels of SMN, the survival of motor neuron protein ( Lefebvre et al , 1995 ), and reduced amounts of Drosha are observed in SMA ( Goncalves et al , 2018 ). The involvement of CBs in the formation of miRNAs encoded in gene clusters more clearly links SMN with the miRNA processing machinery.…”
Section: Resultsmentioning
confidence: 99%
“…In regard to the contribution of CBs to miRNA biogenesis, recent work has implicated miRNA dysregulation as a contributor to spinal muscular atrophy (SMA), the leading genetic cause of infant mortality ( Goncalves et al , 2018 ). Most cases of SMA are caused by insufficient levels of SMN, the survival of motor neuron protein ( Lefebvre et al , 1995 ), and reduced amounts of Drosha are observed in SMA ( Goncalves et al , 2018 ). The involvement of CBs in the formation of miRNAs encoded in gene clusters more clearly links SMN with the miRNA processing machinery.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have shown that Stasimon is an ER-resident, six-transmembrane-pass protein that is essential for mouse embryonic development (Van Alstyne et al, 2018b) and functions in autophagy (Moretti et al, 2018;Morita et al, 2018;Shoemaker et al, 2019). There have also been reports of autophagy dysregulation in SMA, but there is disagreement about whether this pathway is inhibited (Custer and Androphy, 2014;Periyakaruppiah et al, 2016;Rodriguez-Muela et al, 2018) or stimulated (Gonç alves et al, 2018;Piras et al, 2017) by SMN deficiency. Therefore, although autophagy inhibition has been shown to ameliorate the phenotype of SMA mice by blocking p62-mediated SMN degradation (Rodriguez-Muela et al, 2018), it remains to be established whether autophagy defects directly contribute to SMA pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Stasimon Deficiency Is Sufficient to Induce p53 S18 Phosphorylation Recent studies have shown that Stasimon is required for autophagy in cultured mammalian cells (Moretti et al, 2018;Morita et al, 2018;Shoemaker et al, 2019). There have also been reports of autophagy dysregulation in SMA (Custer and Androphy, 2014;Gonç alves et al, 2018;Periyakaruppiah et al, 2016;Piras et al, 2017;Rodriguez-Muela et al, 2018). Therefore, we sought to investigate the possible involvement of Stasimon-dependent autophagy defects in SMA pathogenesis.…”
Section: Stasimon Contributes To Motor Neuron Degeneration In Sma Micementioning
confidence: 99%
“…SMN is an RNA binding protein that performs multiple essential cellular functions including biogenesis of small nuclear ribonucleoproteins (snRNPs) [8] and tra cking of mRNAs to axon terminals [9][10][11]. Furthermore, SMA cells show dysregulated splicing and miRNA processing [12,13], hyperexcitability and impaired Ca 2+ homeostasis [14][15][16], reduced protein synthesis e ciency [10,17,18] and impaired axon growth [11].…”
Section: Page 3/32mentioning
confidence: 99%
“…Cells were incubated with MitoTracker® Red CMXRos (Thermo Fisher Scienti c) at a nal concentration of 100 nM for 15 min and xed with paraformaldehyde (PFA) [13]. The information about antibodies can be found in Supplementary Table 3.…”
Section: Mitotracker® and Immunostaining Of Mnsmentioning
confidence: 99%